Research Progress on Graphite Target Preparation for Accelerator Mass Spectrometry 14C Analysis - LIU Sheng-hua; SHI Hui-xia; JIANG Ya-xin; XU Sheng; LIU Bing-bing (Yankuang ceshi, 2019)
BACKGROUND Accelerator mass spectrometry (AMS) is the most popular technique for radiocarbon analysis. However, yielding high precision and low background 14C data by AMS is hindered by sample preparation. Therefore, improving the stability of graphitization and reducing the carbon contamination in the background helps to produce high quality 14C data and break through the 14C dating upper limit (about 50000ya), further broadening the application range of 14C chronology and isotope tracer. OBJECTIVES To provide basic reference for beginners or more experienced scientists who are going to set up a radiocarbon sample preparation vacuum line and methods. METHODS The development of graphite preparation technology with respect to sample preparation vacuum line apparatus and the underlying principle of H2/Fe, Zn/Fe and Zn-TiH2/Fe methods were reviewed. The advantages and drawbacks of these methods were also discussed. Additionally, the optimization of experimental conditions from the perspective of reductant, catalyst and graphitization temperature, accompanied by the inner relationship with the graphite yield, isotope fractionation and beam performance were emphatically discussed. The sources of carbon contamination and suitable control technology were also argued. RESULTS The optimized graphitization conditions by H2/Fe method was H2/CO2=2-2.5 (V/V), -325 meshes ion powder derived from hydrogen reduction with Fe/C=2-5 (m/m), and graphitization temperature of 500-550℃, while by Zn/Fe method it was Zn/C=50-80 (m/m), -325 meshes ion powder derived from hydrogen reduction with Fe/C=2-5 (m/m), and graphitization temperature of 400-450℃ for Zn reaction tube and 500-550℃ for Fe reaction tube. The carbon contamination originated from each step in the sample preparation procedure, which could be either reduced by high-temperature bake or calibrated by mathematical model, but it required more detailed study to strengthen our knowledge and eliminate the effects on results. CONCLUSIONS Both of the sample preparation methods used and the optimum of graphitization conditions are critical for good performance of the graphite target and the final precision and accuracy of the measurement, especially for ultra-small size samples. However, these effects could be reduced or even eliminated by optimizing the experimental procedures and the graphitization conditions or subtracting by mathematical models.